An 82‐year‐old man with a prosthetic aortic valve and multimicrobial bacteremia - Safiyah Noor Zubair; Soofia Kisana; Cynthia J. Anneski; Imtiaz Ahmed; Sajjad Ashraf Minhas (Journal of the American College of Emergency Physicians Open)
Abstract The patient is an 82‐year‐old male with a past medical history of aortic valve replacement who presented to the emergency department after a fall. He developed atrial fibrillation with a rapid ventricular response and non–ST‐segment–elevation myocardial infarction, leading to hospitalization. During hospital admission, the patient complained of midline thoracic back pain, and an extensive evaluation for this complaint revealed discitis and osteomyelitis with epidural abscess near the T7 and T8 vertebrae that did not result in neurological deficits and required no surgical intervention. A total of 2 blood cultures were reported positive for Actinomyces naeslundii, Streptococcus mitis, Streptococcus oralis, and Abiotrophia defectiva. A transesophageal echocardiogram showed a small vegetation on the aortic prosthetic valve with probable small vegetation on the mitral valve. He was prescribed ceftriaxone intravenously for 12 weeks, followed by amoxicillin 2 g orally twice a day for at least 12 months. A. naeslundii is not commonly known to cause infective endocarditis, whereas S. mitis, S. oralis, and A. defectiva have been reported to do so. One previous case of A. naeslundii was reported to cause prosthetic valve endocarditis as a single infectious agent. To our knowledge, this is the first case report for A. naeslundii as part of multimicrobial bacteremia leading to endocarditis, discitis, and osteomyelitis.